Reviewing a classic but effective method to reduce colour-ring removal by stout-billed birds: a case study in House Sparrows. Issue 1 (2nd January 2020) - Bernat-Ponce, Edgar
ABSTRACT: This study reviews the classic method of using superglue to seal coloured plastic split-rings in 198 House Sparrows. Four birds of 50 individuals recaptured by mist net (8%) and 17 birds of 147 resighted individuals (11.6%) had lost or removed at least one coloured ring. These removal rates are much lower than in similar studies without superglue (18–40%). Sealing the edges of coloured plastic split-rings with superglue is a cheap, safe, efficient, and easy way to reduce their removal in some small bird species with stout beaks.